W. H. Buckley, Sewing-Machines. Coffin & Woodward, Ship Machinery. - Sampson, Davenport and Co. (Tufts Archival Research Center, 2005)
Page image of W. H. Buckley, Sewing-Machines. Coffin & Woodward, Ship Machinery. from the 1872 Boston city directory.